Mindfulness-based treatment approaches clinician's guide to evidence base and applications - Baer, Ruth A. (Practical resources for the mental health professional, 2014)
This book discusses the conceptual foundation, implementation, and evidence base for the four best-researched mindfulness treatments: mindfulness-based stress reduction (MBSR), mindfulness-based cognitive therapy (MBCT), dialectical behavior therapy (DBT) and acceptance and commitment therapy (ACT)